(untitled) (Research, Society and Development, 2021)
The present work evaluated the Water Quality Index (IQA) and the Contamination by Toxics of Ribeirão do Carmo based on the results obtained by the water quality monitoring program carried out by the Mineiro Institute of Water Management (IGAM) between the years of 2010 and 2019 at the sampling station named “RD009”, located in Monsenhor Horta, district of the municipality of Mariana, in the state of Minas Gerais. Nine most representative parameters were adopted for the characterization of water quality and their respective weights according to their relative importance in the calculation of the IQA. Toxic contamination was classified as “Low”, “Medium” or “High” based on the observed concentrations of fourteen toxic parameters. A temporal analysis was performed to monitor the evolution of the IQA and contamination by toxics, as well as a comparison with the criteria recommended in the Normative Deliberation COPAM-CERH No. 01/2008 for class 2. The results show that the IQA along the considered historical series is " medium” while toxic contamination was rated as “high”. The variables thermotolerant coliforms, total phosphorus and total arsenic, which presented results above the maximum allowed by legislation, throughout practically the entire period evaluated, are correlated with the characteristics of land use and occupation in the region. In this sense, it is necessary that public bodies for the management and governance of water resources formulate guidelines and strategies to improve the quality of water in the Ribeirão do Carmo, bearing in mind the health risks to the population of the district of Monsenhor Horta.